Trends in Antibiotic Consumption and Resistance in France Over 20 Years: Large and Continuous Efforts but Contrasting Results. (6th November 2020) - Carlet, Jean; Jarlier, Vincent; Acar, Jacques; Debaere, Olivier; Dehaumont, Patrick; Grandbastien, Bruno; Le Coz, Pierre; Lina, Gerard; Pean, Yves; Rambaud, Claude; Roblot, France; Salomon, Jérôme; et al.
Abstract: Background: Antimicrobial resistance (AMR) is a serious threat to humanity. This paper describes the French efforts made since 2001 and presents data on antimicrobial consumption (AC) and AMR. Methods: We gathered all data on AC and AMR recorded since 2001 from different national agencies, transferred on a regular basis to standardized European data on AC and resistance in both humans and animals. Results: After a large information campaign implemented in France from 2001 to 2005 in humans, AC in the community decreased significantly (18% to 34% according to the calculation method used). It remained at the same level from 2005 to 2010 and increased again from 2010 to 2018 (8%). Contrasting results were observed for AMR. The resistance of Staphylococcus aureus decreased significantly. For gram-negative bacilli, the results were variable according to the microorganism. The resistance of Enterobacteriaceae to third-generation cephalosporins increased, remaining moderate for Escherichia coli (12% in 2017) but reaching 35% in the same year for Klebsiella pneumoniae . Resistance to carbapenems in those 2 microorganisms remained below 1%. Both global AC and resistance to most antibiotics decreased significantly in animals. Conclusions: Antibiotic consumption decreased significantly in France after a large public campaign from 2001 to 2005, but this positive effect was temporary. The effect on AMR varied according to the specific microorganism: The effect was very impressive for gram-positive cocci, variable for gram-negative bacilli, and moderate for E. coli, but that for K. pneumoniae was of concern. The consumption of and resistance to antibiotics decreased significantly in animals.